Deterioro cognitivo en pacientes hipotiroideos atendidos en consulta externa en el Hospital General Isidro Ayora de la ciudad de Loja - Ludeña Severino, Lidia Pilar (2020)
Hypothyroidism is a health problem that affects the social, physical and mental development of people due to the shortage of thyroid hormone production in the thyroid gland resulting from multiple structural abnormalities. The present investigation determined the sex and age group of hypothyroid patients, as well as the presence of cognitive impairment and the relationship between it and hypothyroidism in patients treated in an outpatient setting at the Isidro Ayora General Hospital in the city of Loja, during the period 2014-2017. The type of research is a retrospective cross-sectional study, with a descriptive methodological design and a quantitative approach. A sample of 90 patients was obtained from a total of 450 patients, for the collection of information the test (MoCa) version 7.3 was applied in hypothyroid patients to assess cognitive impairment, which allowed obtaining the following results: 86 female and 4 male cases, according to the age group 13 young adults, 55 middle adults and 22 older adults; Regarding cognitive impairment, 20 cases were negative, 24 probable and 46 positive; There is a statistically significant relationship between the age range and the presence of cognitive impairment, as determined by the Chi-square value of 9.874 with 2 degrees of freedom and the Cramer's V coefficient of 0.331. Therefore, it is concluded that advanced age constitutes a risk factor for the development of cognitive deterioration in hypothyroid patients. KEY WORDS: Hypothyroidism, Thyroid hormones, MoCa, Cognitive Impairment